Teaching English for Specific Purposes: Content Language Acquisition vs General Language Acquisition - Sulindra, Eric (Widya Mandala Catholic University Surabaya, 2019)
An approach to English for Specific Purposes (ESP) teaching and learning, Content Language Integrated Learning (CLIL) has been subjects for studies. The approach has worked well and has brought the learners forward from the previous stage. The language learning outcomes in CLIL are usually made contextual, functional and communicative. In this study, the students regarded CLIL as relevant and to deliver the English language teaching in the context of their field. On the other hand, the General Language has provided support up to the extent of explaining the language grammatical points (using the terms such as complex, compound, subject, predicate, objects). Then, authentic learning materials are regarded as being relevant to their interest and the subject matter. The CLIL approach are recommended to be applied under constant observation and evaluation since the ESP world is various and multi-context. This approach is supposed to be adjusted with the local environment, students’ interest, according to the standard ESP need analysis to arrange the lesson plan. Further research on how CLIL is able to influence the students’ language mastery in a specific field is subject to be systematically conducted.